DE LA FACHADA AL RETABLO. UN RECORRIDO POR LOS TEMPLOS MURCIANOS DEL SIGLO XVIII - de la Peña Velasco, Concepción; Hernández Albadalejo, Elías (Imafronte, 1994)
The portal and main altarpiece are the two great image-ornamented elements on the route taken by churchgoers as they go in through the main door and up to the high altar. Moreover, they are the areas which command greatest attention and, without entering into any other considerations, depend on the type of religious architecture that surrounds them. There are obvious relationships between the main façade and altarpiece or, to be more precise, between the portal and altarpiece. These relationships are the subject of analysis, especially with regard to their architectural design and iconography.